2022
DOI: 10.1002/anie.202204088
|View full text |Cite
|
Sign up to set email alerts
|

Diazaphospholene‐Catalyzed Radical Reactions from Aryl Halides**

Abstract: Diazaphospholenes are widely used as hydride transfer catalysts, however their use in radical reactions is a recently emerging area. Here, we show prior stoichiometric radical cyclizations of aryl iodides mediated by diazaphospholene hydrides are made catalytic by the combination of phenylsilane and alkali metal salts to regenerate the diazaphospholene hydride. The scope was expanded to include aryl bromides, which benefit from visible light irradiation. Twenty one substrates underwent cyclization, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Given recent advances toward the cyclizations of organohalides across olefins, we were motivated to investigate the radical cyclization of 1a instead of debromination of methyl 4-bromobenzoate. By using 1a as a model substrate to test the reactivity, we were pleased to isolate the cyclization product in 92% yield (Table S1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given recent advances toward the cyclizations of organohalides across olefins, we were motivated to investigate the radical cyclization of 1a instead of debromination of methyl 4-bromobenzoate. By using 1a as a model substrate to test the reactivity, we were pleased to isolate the cyclization product in 92% yield (Table S1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, precious metal–based photoredox catalysis, organic photocatalyst, and tris­(trimethylsilyl)­silane have demonstrated the substantial advances in the generation of carbon-centered radicals from a variety of organic halides, which significantly expand the reactions of carbon-centered radicals (Figure a). Other organic halides reduction reactions such as diazaphospholene-catalyzed reduction of organohalides, o -phosphinophenolate catalyzed reduction of aryl halides, and dechlorination of aryl chlorides using CO 2 ·– as a reductant have also been reported. Despite all this progress, there remains a strong interest in developing a green, general, and benign protocol for the reduction of organic halides and expanding the repertoire of reactions of carbon-centered radicals.…”
mentioning
confidence: 99%
“…17 These pioneering studies laid the foundation for subsequent applications of NHP radicals in organic syntheses. Recently, several stoichiometric or catalytic radical reactions, such as hydrodehalogenations and cyclizations, [18][19][20] enabled by NHP have been developed.…”
Section: Jin-pei Chengmentioning
confidence: 99%
“…Recently, Cramer et al 19 and Speed et al 20 have independently reported NHP-catalyzed reductive radical cyclization of organic halides by using different base-reductant combinations (DBU/ HBpin and Cs 2 CO 3 /PhSiH 3 , Scheme 19). The key to the success of these NHP-catalyzed reductions is the combinatorial use of bases and hydrogen sources to regenerate NHPs.…”
Section: Nhp-catalyzed Reductive Radical Cyclizationmentioning
confidence: 99%
“…[10] A recent study indicated that aryl radicals and radical cations would be distinguishable from the resulting carbon radicals. [11] Our previous research has highlighted this challenge. We recently reported a method to generate carbon radicals from the corresponding aliphatic alcohols.…”
Section: Introductionmentioning
confidence: 99%